2006
DOI: 10.1097/01.pec.0000210176.48386.ae
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Life-threatening Event or Child Abuse?

Abstract: Children with apparent life-threatening events (ALTEs) often pose a diagnostic and management dilemma in a pediatric emergency department. Although the term ALTE is nonspecific and symptoms are vague, it may have alarming connotations and may signal serious life threatening conditions. It may be a subtle presentation of child abuse. We report an infant who was presented with an ALTE and subsequently determined to have subdural hematoma caused by nonaccidental injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
3
1
1
Order By: Relevance
“…The relationship between ALTEs and child abuse is well documented, and the literature suggests that up to 10% of ALTEs may be attributable to abuse. [22][23][24][25] We caution, however, against making recommendations for changes in clinical practice on the basis of our findings; although the rate of positive SS results in this population was higher than expected, the proportion of children with ALTEs who underwent an SS was small. During the same 4-year time period as in the current study, 421 children were discharged from our ED with a diagnosis of ALTE.…”
Section: Figurecontrasting
confidence: 62%
“…The relationship between ALTEs and child abuse is well documented, and the literature suggests that up to 10% of ALTEs may be attributable to abuse. [22][23][24][25] We caution, however, against making recommendations for changes in clinical practice on the basis of our findings; although the rate of positive SS results in this population was higher than expected, the proportion of children with ALTEs who underwent an SS was small. During the same 4-year time period as in the current study, 421 children were discharged from our ED with a diagnosis of ALTE.…”
Section: Figurecontrasting
confidence: 62%
“…Younger children can be more easily irritated, are hard to appease, and are relatively unable to defend themselves, fight back, or report their injury. [7–9] This may explain the lower mean age in the abuse group than that in the neglect group. In addition, there were more boys than girls in this study, which is similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Denver involving children who died of AHT found that the most common presenting complaint was apnea; only 1 of 36 had a presenting complaint of trauma (Graupman & Winston, 2006). In Vellody's study of infants with a history of ALTE (Duhaime et al, 1992), 4 of 108 infants were eventually found to have sustained AHT (Waseem & Pinkert, 2006). All four had other findings suspicious for abuse including skin contusions, fractures, retinal hemorrhages, or a history given by a parent that the infant had been shaken.…”
Section: Clinical Presentationmentioning
confidence: 96%